The efficacy of video-based marker-less tracking system in gait analysis - Ong, A.; Sujae, I. H. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
An alternative to the 3D motion capture is the marker-less 3D video tracking system. Though not rigorously tested yet, the 3D marker less video tracker would break new grounds if it is possible of extracting similar kinematic parameters as the gold standard 3D marker based motion capturers. The aim of our study is to explore the feasibility of a video based marker-less system which is as accurate and precise as its marker based counterpart. A series of gait analysis tests were carried out on ten subjects with a marker and marker-less system simultaneously. The study suggests potential applications in gait analysis in the academic classrooms and clinical settings where observations of anatomical motions provide meaningful feedback.